2022
DOI: 10.1089/heq.2021.0149
|View full text |Cite
|
Sign up to set email alerts
|

Black/White Disparities in Obesity Widen with Increasing Rurality: Evidence from a National Survey

Abstract: Background Racial health disparities in obesity and obesity-related conditions and behaviors are well documented, although a small body of research suggests that geographic factors (e.g., socioeconomic status [SES] and rural/urban status) may alter the magnitude of these disparities. Methods This study explored how rurality moderates black/white health disparities using a nationally representative sample from the 2012 Behavioral Risk Factor Surveillance System ( … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 88 publications
1
7
0
Order By: Relevance
“…Black‐White differences in mortality are widest in rural areas, and those differences have widened over time 55 . Similar results have been found with obesity: rural areas have the highest rates of obesity, but also Black‐White differences in the rates of having obesity are largest in rural areas 56 . Furthermore, a 2021 study 57 found critical regional differences in the rural health and mortality penalty in the US, where rural mortality rates are worse in the rural south compared to other rural areas.…”
Section: Introductionsupporting
confidence: 68%
“…Black‐White differences in mortality are widest in rural areas, and those differences have widened over time 55 . Similar results have been found with obesity: rural areas have the highest rates of obesity, but also Black‐White differences in the rates of having obesity are largest in rural areas 56 . Furthermore, a 2021 study 57 found critical regional differences in the rural health and mortality penalty in the US, where rural mortality rates are worse in the rural south compared to other rural areas.…”
Section: Introductionsupporting
confidence: 68%
“… 26 The effect of comorbidities on race disparity was hypothesized, as there is evidence that African Americans are more likely to experience comorbidities such as obesity and diabetes compared to white patients. 11 , 27 However, previous studies aimed at investigating this hypothesis found that the number of comorbidities does not significantly contribute to racial disparities in DBS utilization for PD patients. 3 , 11 Our findings revealed that the ET-DBS cohort had a significantly higher proportion of patients with moderate number of comorbidities compared to the PD-DBS cohort (32.5% vs %24%), indicating more liberal selection criteria for DBS surgery among ET patients than PD patients.…”
Section: Discussionmentioning
confidence: 99%
“…One such measure is the Index of Relative Rurality (IRR) [49], which is calculated using population size, population density, distance to nearest metropolitan area, and percent urban population. The IRR has been used in several recent studies on health and aging, including health services utilization [50], geographic inequities in healthcare providers [51], availability of hospice care [52], opioid prescribing patterns [53], obesity [54], and COVID-19-related outcomes [55,56].…”
Section: Defining Rurality: Methodological Considerationsmentioning
confidence: 99%
“…A 2019 study showed that although White rural older adults reported less social isolation than their urban counterparts, the association was reversed among some racial and ethnic minorities, where rural Black older adults experienced significantly greater social isolation than urban Black older adults [178]. Another recent study found that the well-documented Black-White differences in obesity were significantly worse in rural areas compared to urban areas [54].…”
Section: Special Populations In Rural Areasmentioning
confidence: 99%